2004
DOI: 10.1152/ajpcell.00105.2004
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin reverses rundown of L-type Ca2+ channels in guinea pig ventricular myocytes

Abstract: Calmodulin (CaM) is implicated in regulation of Ca(2+) channels as a Ca(2+) sensor. The effect of CaM on rundown of L-type Ca(2+) channels in inside-out patch form was investigated in guinea pig ventricular myocytes. Ca(2+) channel activity disappeared within 1-3 min and did not reappear when the patch was excised and exposed to an artificial intracellular solution. However, application of CaM (0.03, 0.3, 3 microM) + 3 mM ATP to the intracellular solution within 1 min after patch excision resulted in dose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
53
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 44 publications
14
53
0
Order By: Relevance
“…We previously found that run-down of L-type Ca 2+ -channel activities is reversed by CaM + ATP (14) and that CaMKII-mediated phosphorylation is also involved in the maintenance of basal activity of the channels (15). In the present study, we have confirmed that playing distinct roles, both CaM and CaMKII are required in the reversal of run-down of Ca 2+ -channel activities.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We previously found that run-down of L-type Ca 2+ -channel activities is reversed by CaM + ATP (14) and that CaMKII-mediated phosphorylation is also involved in the maintenance of basal activity of the channels (15). In the present study, we have confirmed that playing distinct roles, both CaM and CaMKII are required in the reversal of run-down of Ca 2+ -channel activities.…”
Section: Discussionsupporting
confidence: 84%
“…3A (middle lane, open circle), 5 min after run-down, different concentrations of CaM were applied. However, even with concentrations of 7 μM, 10 times of 0.7 μM, the concentration that we previously used (14), no obvious recovery of the channel activity was observed. The averaged relative channel activities from 5 to 10 min after the formation of inside-out patches are 28.2 ± 11.1% (n = 4), 23.5 ± 3.2% (n = 4), and 42.5 ± 11.2% (n = 6) for CaM at 0.7, 2.1, and 7 μM, respectively, indicating that the time-dependent attenuation of CaM's effects in the reversal of run-down of Ca 2+ channels is not due to the insufficient dose of CaM.…”
Section: Bell-shaped Concentration-dependent Effects Of Cam On Camentioning
confidence: 65%
See 1 more Smart Citation
“…''Mode 2'' gating was discovered as a pharmacological effect of the dihydropyridine Bay K8644 (4), but subsequent work has implicated reversible protein phosphorylation of the channel by calcium͞calmodulin-dependent protein kinase type II (CaMKII) in the regulation of mode 2 gating in cells that were not treated with dihydropyridines (5). Although the molecular mechanism of this effect and its physiological consequences are only beginning to be investigated (6)(7)(8)(9), it is likely that unregulated mode 2 gating would be cytotoxic because the individual channel openings in mode 2 are Ͼ10 times longer on average than the openings in mode 1.…”
mentioning
confidence: 99%
“…Our previous study has shown that the run-down of Ca V 1.2 activity is reversed by CaM and ATP (Xu et al, 2004). The direct binding of CaM with the IQ motif of the Ca 2 + -channel a1-subunit has been reported to be involved in the molecular mechanism by which it exerts its Ca 2 + -dependent effects, namely, CDI and CDF.…”
Section: Discussionmentioning
confidence: 99%